Unexpected diversity in the Pseudepipona lativentris species-group (Hymenoptera: Vespidae: Eumeninae) - Fateryga, Alexander V.; Selis, Marco (Zootaxa, 2024)
The Pseudepipona lativentris-group includes the species of the nominotypical subgenus of the genus Pseudepipona de Saussure, 1856 with long setae on the gena, the scutum, and the propleuron (former subgenus Trichepipona Blüthgen, 1951). Five species and two additional subspecies were hitherto recognized in this group, while the present taxonomic revision revealed the existence of eight species: P. beckeri (Morawitz, 1867) (Russia, Kazakhstan), P. cretensis Blüthgen, 1942 (endemic to Crete, Greece), P. cypria Blüthgen, 1942, stat. nov. (?Turkey, Cyprus, ?Lebanon, Israel and Palestine), P. falsa (Kostylev, 1927), stat. resurr. (Iran, Turkmenistan, Tajikistan, Uzbekistan, Kyrgyzstan, Kazakhstan), P. gineri (von Schulthess, 1934) (endemic to Ibiza and Formentera, Spain), P. lativentris (de Saussure, 1855) (France, Switzerland, Portugal, Spain, Italy, Croatia, Morocco, Tunisia, Azerbaijan, Turkey, ?Lebanon), P. rubricans Kurzenko, 1976, stat. nov. (Kyrgyzstan, Kazakhstan, China), and P. vicina Gusenleitner, 1973 (Afghanistan, Uzbekistan, Kyrgyzstan, Kazakhstan, India). A complete diagnosis is provided for each species, as well as an identification key. A map detailing the geographic distribution of all species is presented. Lectotypes are designated for Odynerus beckeri Morawitz, 1867 and O. falsus Kostylev, 1927.